Integrated Analysis of Transcriptome and Secretome From Umbilical Cord Mesenchymal Stromal Cells Reveal New Mechanisms for the Modulation of Inflammation and Immune Activation - Cruz-Barrera, Mónica; Flórez-Zapata, Nathalia; Lemus-Diaz, Nicolás; Medina, Carlos; Galindo, Cristian-Camilo; González-Acero, Lorena-Xiomara; Correa, Luz; Camacho, Bernardo; Gruber, Jens; Salguero, Gustavo (Frontiers in Immunology, 2020)
Mesenchymal stromal cells (MSC) have been used in over 800 clinical trials with encouraging results in the field of transplant medicine and chronic inflammatory diseases. Today, Umbilical Cord (UC)-derived MSC are the second leading source used for clinical purposes, mainly due to its easy access and superior immune-modulatory effects. Although the underlying molecular mechanisms of immune-suppressive activities have not been fully understood, research over the last decade strongly suggests that MSC-mediated benefits are closely related to the activation of secretome networks. Nevertheless, recent findings also point to cytokine-independent mechanisms as key players of MSC-mediated immune modulation. Here, we set up a robust in vitro immune assay using phytohemagglutinin- or anti-CD3/CD28-treated human peripheral blood mononuclear cells in cell-to-cell interaction or in cell-contact independent format with UC-MSC and conducted integrated transcriptome and secretome analyses to dissect molecular pathways driving UC-MSC-mediated immune modulation. Under inflammatory stimuli, multiparametric analyses of the secretome led us to identify cytokine/chemokine expression patterns associated with the induction of MSC-reprogrammed macrophages and T cell subsets ultimately leading to immune suppression. UC-MSC transcriptome analysis under inflammatory challenge allowed the identification of 47 differentially expressed genes, including chemokines, anti- and pro-inflammatory cytokines and adhesion molecules found also in UC-MSC-immunosupressive secretomes, including novel candidates such as CD131, CD366, and soluble IL-2R. This study enabled us to track functionally activated UC-MSC during immune suppression and opened an opportunity to explore new pathways involved in immunity control by UC-MSC. We propose that identified immunomodulatory molecules and pathways could potentially be translated into clinical settings in order to improve UC-MSC-therapy quality and efficacy.